2012
DOI: 10.3892/etm.2012.475
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MTA2 overexpression and tumour progression in esophageal squamous cell carcinoma

Abstract: Abstract. The aim of this study was to clarify the clinicopathological outcome and prognostic significance of metastasis-associated gene 2 (MTA2) in esophageal squamous cell carcinoma (ESCC). Immunohistochemical staining for MTA2 was performed on surgical specimens obtained from 162 patients with ESCC. Relationships between MTA2 expression and clinicopathological factors, including prognosis, were analyzed. Significant correlations were noted among MTA2 overexpression and TNM clinical classification staging, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…MTA2 has been linked to tumour invasion depth, regional lymph node metastasis, distant metastasis, and poor long-term survival rates independent of age or gender in patients with esophageal squamous cell carcinoma [29], gastric cancer [13], non-small-cell lung cancer [30], and colorectal cancer [31]. Consistent with these studies, we observed higher MTA2 expression in tumour tissues compared with normal tissues and in all the RCC cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…MTA2 has been linked to tumour invasion depth, regional lymph node metastasis, distant metastasis, and poor long-term survival rates independent of age or gender in patients with esophageal squamous cell carcinoma [29], gastric cancer [13], non-small-cell lung cancer [30], and colorectal cancer [31]. Consistent with these studies, we observed higher MTA2 expression in tumour tissues compared with normal tissues and in all the RCC cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…MTA2 plays an important functional role in various processes related to tumorigenesis and metastasis in some solid tumors, including nasopharyngeal carcinoma, glioma, and pancreatic ductal adenocarcinoma . Recent reports have suggested that MTA2 is overexpressed in ESCC or PDAC tissues, and this overexpression is significantly correlated with lymph node metastasis and 5‐year survival rates . In the present study, the results obtained by using a clinicopathological database and TCGA database of oral tumor tissues indicated that MTA2 was positively associated with a high tumor grade and the overall survival of patients.…”
Section: Discussionsupporting
confidence: 47%
“…Our previous study suggested that MTA2 knockdown inhibits human glioma cell proliferation, induces cell cycle arrest at the G0/G1 phase, and modulates p21 and p53 expression . Moreover, MTA2 inhibition suppresses cell viability, invasion, and tumor growth by affecting the expression of p21, p27, p53, and cyclin D1 in nasopharyngeal carcinoma and breast cancer cells . Shi et al reported a significant relationship between the expression of nuclear MTA2 and Ki‐67 and the overall survival of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also showed strong expression of MTA2 in the ovary, heart, and lung. The upregulation of MTA2 has been reported in many cancers, such as cervical cancer [111], hepatocellular carcinoma [114], osteosarcoma [16], lung cancer [115], thymoma [116], esophageal squamous cell carcinoma [117], pancreatic ductal adenocarcinoma [118], gastric cancer [119], breast cancer [120], and glioma [121], contributing to more aggressive malignant phenotypes of cancer. MTA2 was reported to be nuclear in most reports [11,113,122]; however, in a recent report, Liu (2) et al [115] demonstrated using immunohistochemistry and immunofluorescence technologies that MTA2 was distributed in both the nucleus and cytoplasm in normal and cancer cells.…”
Section: Mta2mentioning
confidence: 99%